2009
DOI: 10.24198/pjd.vol21no2.14094
|View full text |Cite
|
Sign up to set email alerts
|

Changes of occlusal plane inclination after orthodontic treatment with four premolars extraction in dento-alveolar bimaxillary protrusion cases

Abstract: The purpose of this study was to find out whether there were changes in occlusal plane inclination after fixed orthodontic treatment of bimaxillary protrusion cases where extraction of four first premolars were needed using the standard Edgewise appliances. The sample were fourteen orthodontic patients, aged above sixteen years old, no sexual discrimination, treated with fixed appliances at Orthodontic Specialist Clinic Faculty of Dentistry Universitas Padjadjaran. The method was pre-post design which compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Class II elastic is often used in treating patients with skeletal Class II malocclusion, which can cause rotation of the occlusal plane downward and backward. 16,18,21 There was a significant increase in the mandibular incisor inclination (L1-MP/°) and vertical position of mandibular first molars (L6-MP (mm)) before and after non-extraction treatment in this study. These results correlate with the findings of Janson et al 22 which have shown that there was a change in the mandibular incisor inclinations to the anterior and extrusion of the mandibular first molar.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Class II elastic is often used in treating patients with skeletal Class II malocclusion, which can cause rotation of the occlusal plane downward and backward. 16,18,21 There was a significant increase in the mandibular incisor inclination (L1-MP/°) and vertical position of mandibular first molars (L6-MP (mm)) before and after non-extraction treatment in this study. These results correlate with the findings of Janson et al 22 which have shown that there was a change in the mandibular incisor inclinations to the anterior and extrusion of the mandibular first molar.…”
Section: Discussionsupporting
confidence: 46%
“…26 If the anterior teeth are retracted to prevent the posterior teeth from moving forward, posterior anchorage can be added by involving the second molar. 18 In this study, we have found that there was a significant reduction of maxillary central incisor inclination, maxillary central incisor and mandibular first molar extrusions, and mandibular central incisor intrusions. This finding correlates with Demir et al 26 who have found a significant reduction in the maxillary incisor inclination and an increased mandibular incisor inclination.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In a growing facial skeleton, the position of OP is determined largely by the vertical growth of the maxillary teeth, and the inclination of the OP is determined largely by the growth of the dentoalveolar bone [ 2 ]. Besides the growing factors mentioned above, the maintenance or changing of the OP during orthodontic treatment depends on mesial molar movement, vertical control of the maxillary and mandibular molars, and extrusion and intrusion of incisors [ 1 , 20 ]. The amount of mesial molar movement is often very little in non-extraction case, so only the other two factors were considered.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that the inclination of the OP relates to facial types, with the class II facial types having a relatively steep angle, bending toward horizontal as the patient approaches class III [ 13 ]. Additionally, different orthodontic diagnosis and treatment plans could be made depending on the type of malocclusion and therapeutic goals, which might or might not change the OP [ 1 , 19 , 20 ]. Determination of OP is desirable to meet the demands of both esthetics [ 6 ] and function [ 5 ].…”
Section: Introductionmentioning
confidence: 99%